Dietary Supplements as a Major Cause of Anti-doping Rule Violations - Lauritzen, Fredrik (Frontiers in Sports and Active Living, 2022)
Dietary supplements encompass a large heterogenic group of products with a wide range of ingredients and declared effects used by athletes for a multitude of reasons. The high prevalence of use across all sports and level of competition, combined with the well-documented risks of such products containing prohibited substances have led to several doping cases globally. Despite being a considerable concern and persistent focus of sport organizations and anti-doping agencies, the magnitude of anti-doping rule violations associated with supplement use is not well-known. This study examines 18-years of doping controls of a national anti-doping program to determine the relationship between the presence of prohibited substances in athlete's doping samples and the use of dietary supplements. In 26% (n = 49) of all the analytical anti-doping rule violation cases in the period 2003–2020 (n = 192), the athlete claimed that a dietary supplement was the source of the prohibited substance causing an adverse analytical finding. Evidence supporting this claim was found in about half of these cases (n = 27, i.e., 14% of all analytical ADRV's). Stimulants were the most prevalent substance group linked to supplements (n = 24), of which methylhexanamine was associated with 16 cases. High risk products were predominantly multi-ingredient pre-workout supplements (n = 20) and fat-burning products (n = 4). Anti-doping organizations should develop strategies on how to assist athletes to assess the need, assess the risk and assess the consequences of using various dietary supplements.